Novel Ru(II)-bipyridine/phenanthroline-lapachol complexes as potential anti-cancer agents - De Grandis, Rone Aparecido; Costa, Analu Rocha; Moraes, Carlos André Ferreira; Sampaio, Natália Zaneti; Cerqueira, Igor Henrique; Marques, Wellington Garcia; Guedes, Adriana Pereira Mundin; de Araujo-Neto, João Honorato; Pavan, Fernando Rogério [UNESP]; Demidoff, Felipe Cerqueira; Netto, Chaquip Daher; Batista, Alzir Azevedo; et al. (Elsevier, 2022)
For the first time, we herein report on the syntheses of two new Ru(II)/bipyridine/phenanthroline complexes containing lapachol as ligand: complex (1), [Ru (bipy)2(Lap)]PF6 and complex (2), [Ru(Lap)(phen)2]PF6, where bipy = 2,2′-bipyridine and ph en = 1,10-phenanthroline; Lap = lapachol (2-hydroxy-3-(3-methylbut-2-en-1- yl)naphthalene-1,4-dione). The complexes were synthesized and characterized by elemental analyses, molar conductivity, mass spectrometry, ultraviolet-visible and infrared spectroscopies, nuclear magnetic resonance (1H, 13C), and single crystal X-ray diffraction, for complex (2). In addition, in vitro cytotoxicity was tested against six cancer cells: A549 (lung carcinoma); DU-145 (human prostate carcinoma); HepG2 (human hepatocellular carcinoma), PC-3 (human prostate adenocarcinoma); MDA-MB-231 (human breast adenocarcinoma); Caco-2 (human colorectal adenocarcinoma), and against two non-cancer cells, FGH (human gingival normal fibroblasts) and PNT-2 (prostate epithelial cells). Complex (1) was slightly more toxic and selective than complex (2) for all cell lines, except against the A549 cells, where (2) was more potent than complex (1). The complexes induced an increase in the reactive oxygen species, and the co-treatment with N-acetyl-L-cysteine remarkably suppressed the ROS generation and prevented the reduction of cell viability, suggesting that the cytotoxicity of the complexes is related to the ROS-mediated pathway. Further studies indicated that the complexes may bind to DNA via minor groove interaction. Our studies also revealed that free Lap induces gene mutations in Salmonella Typhimurium, nevertheless, the complexes demonstrated the absence of genotoxicity by the Ames test. The present study provides a relevant contribution to understanding the anti-cancer potential and genetic toxicological events of new ruthenium complexes containing the lapachol molecule as a ligand.
Keywords: Cytotoxicity; Genotoxicity; Lapachol; Reactive oxygen species; Ruthenium complexes